Internalisasi Budaya Sekolah 3S (Senyum, Sapa dan Salam) dalam Meningkatkan Nilai Kesopanan di MTsN 2 Ponorogo - Nazira, Diah Ayu; Yusuf, S. Maryam; Adham, M Januar Ibnu (Institut Agama Islam Negeri Ponorogo, 2023)
The background of this study originated from the found lack of politeness value of students in class IX MTsN 2 Ponorogo. From the results of observations that have been carried out previously, researchers found several students who behave rudely and speak impolitely, ethics in madrasa students have not been fully implemented, lack of friendly attitudes and respectful attitudes, some students lack a caring attitude towards their surroundings. This study aims to describe the internalization of the 3S school culture (Senyum, Sapa, and Salam) in increasing the value of politeness at MTsN 2 Ponorogo. This research uses a qualitative approach with a case study research type. While the data analysis technique used is the Miles, Huberman, and Saldana method which consists of 4 stages, namely data collection, data condensation, data presentation, and verification. The results of the study found that 1) the internalization of 3S culture at MTsN 2 Ponorogo begins with habituation. All madrasah residents are accustomed to implementing a culture of smiles, greetings, and greetings while in the madrasah environment. 2) The inhibiting factors for the internalization of the 3S culture are the effectiveness of teachers who are not optimal, environmental factors and peers. While the supporting factors are cooperation and support from madrasah stakeholders and parents who participate in assisting in the implementation of the program. 3) The impact of internalizing the 3S culture is the behavior of madrasah residents who increasingly show exemplary and as expected. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan internalisasi budaya sekolah 3S (Senyum, Sapa, dan Salam) dalam meningkatkan nilai kesopanan di MTsN 2 Ponorogo. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Sementara teknik analisis data yang digunakan adalah dengan metode Miles, Huberman, dan Saldana yang terdiri dari 4 tahap yakni pengumpulan data, kondensasi data, penyajian data, dan verifikasi. Hasil penelitian ditemukan bahwa 1) internalisasi budaya 3S di MTsN 2 Ponorogo dimulai dengan pembiasaan. Seluruh warga madrasah dibiasakan untuk menerapkan budaya senyum, sapa, dan salam selama dilingkungan madrasah. 2) faktor penghambat internalisasi budaya 3S yakni efektifitas guru yang belum maksimal, faktor lingkungan dan teman sebaya. Sedangkan faktor pendukung nya yakni kerja sama dan dukungan dari para stakeholder madrasah dan orangtua yang turut serta membantu dalam pelaksanaan program. 3) dampak internalisasi budaya 3S adalah perilaku warga madrasah yang semakin menunjukkan keteladanan dan sesuai dengan yang diharapkan.